Does Spirituality In The Workplace Reflect The Relationship Between Accounting And Corruption Prevention? - Pupung Purnamasari; Annisa Nadiyah Rahmani; Rudy Hartanto (Universitas Muhammadiyah Malang, 2020)
The purpose of this study was to discuss and analyze the implementation of accounting for acts of corruption prevention in Indonesia by using spirituality in the workplace. The respondents in this study were professional people (forensic accountants at BPKP and BPK Indonesia) who were the right representatives to improve the quality of the generalization of research results. This study uses quantitative descriptive analysis and structural equation modeling (SEM) with a sample of 189 respondents. The results of this study indicate a positive relationship between the application of forensic accounting and corruption prevention, a positive relationship between the implementation of forensic accounting and spirituality in the workplace, and a positive relationship between spirituality in the workplace and corruption prevention. In particular, the results illustrated that spirituality in the workplace positively influenced the relationship between the implementation of forensic accounting and corruption prevention. This finding provides a sign for Government Agencies, especially BPK and BPKP auditors to improve their understanding of the implementation of Forensic Accounting for forensic auditors.